Intranasal treatment with luteinising hormone releasing hormone agonist in women with endometriosis. Issue 6406 (3rd December 1983) - Shaw, R W; Fraser, H M; Boyle, H
Abstract : An agonist analogue of luteinising hormone releasing hormone (buserelin) was successfully used to treat women with endometriosis. A dose of 200 micrograms administered intranasally thrice daily was found to be effective in five patients, in whom the endometriotic lesions resolved after six months' treatment. Failure occurred in a sixth patient, who received only 400 micrograms once daily. Anovulation was induced in all subjects together with suppression of menstruation after the first month of treatment. Symptoms of abdominal pain, dysmenorrhoea, and dyspareunia were relieved during treatment, and one previously infertile patient conceived within two months of stopping treatment. No side effects were reported with this dosage, and the results suggest a new form of treatment for patients with endometriosis.